Accès À L'eau Pour Les Agricultrices Saheliennes : Enjeux Pour Une Démocratie Inclusive - Thioune, Ramata Molo; Alissoutin, Rosnert Ludovic (Book collections on Project MUSE., 2014)
This collective work was conducted within the context of the research project entitled "Effectiveness of women's economic rights: the case of access to water for agricultural use in Mauritania, Niger and Senegal". Initiated by the African Network for Integrated Development (RADI) and the International Development Research Centre (IDRC), it aims to explain the origins, manifestations and consequences of the gender divide with regards to access, use and control of productive water. Beyond its significance for research, this issue is also relevant to the dynamic protection of women's economic rights in the Sahelian environment where the difficult collection of water and the issues pertaining to poverty generate tensions between various consumption needs and interests. The correlation between the research results obtained in the three countries emerges as a critical lesson on the investigative approach, which is fundamentally marked by gender, participation and comparison, and also outlines the ways in which to promote women's equitable access to economic resources, in particular their access to water reserved for agricultural use. In this light, one of the novelties of this sub-regional scientific initiative is the establishment of a transnational advocacy committee responsible for promoting the implementation of the recommendations of the research. This means that the research-action process is far from being completed.